Psychological distress level survey of Islamic boarding school student - Khairunnisa; Mahdia Fadhila; Yulia Hairina (Universitas Muhammadiyah Banjarmasin, 2024)
Psychological distress is an unpleasant subjective state characterized by two main aspects, namely depression and anxiety. The purpose of this study was to determine the psychological distress level of Islamic boarding school students and factors that influence the occurrence of psychological distress. The research method used in this research is a survey. Sampling technique using simple random sampling method with criteria is student who is currently studying at the Islamic Boarding School in Banjarmasin aged 13–19 years. Respondents amounted to 244 students. The measuring instrument used is the Kessler Psychological Distress scale (K-10) adapted and validated in Indonesian language. The research results show psychological distress of students is in the moderate category both in terms of depression and anxiety. The factors that influence the occurrence of psychological distress were situational factors, sociodemographic factors, personal resources, and stress-related factor.